Deployment of the cowpea aphid resistance gene for cowpea improvement in Ghana - Kusi, F. (University of Ghana, 2014)
Resistance to the cowpea aphid is important component of integrated pest management of cowpea cropping systems most especially at the vegetative stage. The objective of this study was to demonstrate the effectiveness of the aphid resistance locus identified in advanced breeding line SARC 1-57-2 in reducing damage from the cowpea aphid in Ghana. Using an F2 population developed from Apagbaala x SARC 1-57-2, the resistance locus was tagged with the SSR marker CP 171F/172R with a recombination fraction of 5.91%. Based on the CP 171F/172R, recurrent marker assisted backcrossing was carried out to introduce the resistance locus into the susceptible cultivar, Zaayura. This led to the development of several BC4F3 lines that are isogenic except for the region of the resistance locus. In field tests under no insecticide protection, the BC4F3 lines carrying the dominant marker allele suffered 3% loss of biomass and 4% loss of grain yield compared with plots protected with recommended insecticides. The BC4F3 lines carrying the recessive marker allele recorded 12% loss of biomass and 33% reduction in grain yield compared with the sprayed plots. The resistance locus did not influence the number of days to flowering or maturity and no pleiotropic effects were observed in terms of plant morphology or seed characteristics. In all segregating populations analysed, the locus segregated as a single Mendelian gene. Stability of the resistance locus was conducted at 18 locations covering six important cowpea growing Regions in Ghana. The range of damage by the pest on resistant and susceptible progenies were consistent across locations, and did not support the hypothesis of existence biotypes of the insect (based on differences in feeding damage on different varieties) in Ghana. This stability in performance places a premium on the resistance locus in improving cowpea cultivars developed for different agro-climatic regions of the country for resistance to the pest. The study has demonstrated the effectiveness of an insect resistance locus in significantly reducing insect damage under typical cowpea production conditions in Ghana
Thesis (PhD) - University of Ghana, 2014